Statins do not alter the incidence of mesothelioma in asbestos exposed mice or humans - Robinson, C.; Alfonso, Helman; Woo, S.; Walsh, A.; Olsen, N.; Musk, A.; Robinson, B.; Nowak, A.; Lake, R. (Public Library of Science, 2014)
Mesothelioma is principally caused by asbestos and may be preventable because there is a long latent period between exposure and disease development. The most at-risk are a relatively well-defined population who were exposed as a consequence of their occupations. Although preventative agents investigated so far have not been promising, discovery of such an agent would have a significant benefit world-wide on healthcare costs and personal suffering. Statins are widely used for management of hypercholesterolemia and cardiovascular risk; they can induce apoptosis in mesothelioma cells and epidemiological data has linked their use to a lower incidence of cancer. We hypothesised that statins would inhibit the development of asbestos-induced mesothelioma in mice and humans. An autochthonous murine model of asbestos-induced mesothelioma was used to test this by providing atorvastatin daily in the feed at 100 mg/kg, 200 mg/kg and 400 mg/kg. Continuous administration of atorvastatin did not alter the rate of disease development nor increase the length of time that mice survived. Latency to first symptoms of disease and disease progression were also unaffected. In a parallel study, the relationship between the use of statins and development of mesothelioma was investigated in asbestos-exposed humans. In a cohort of 1,738 asbestos exposed people living or working at a crocidolite mine site in Wittenoom, Western Australia, individuals who reported use of statins did not have a lower incidence of mesothelioma (HR = 1.01; 95% CI = 0.44-2.29, p = 0.99). Some individuals reported use of both statins and non-steroidal anti-inflammatory drugs or COX-2 inhibitors, and these people also did not have an altered risk of mesothelioma development (HR = 1.01; 95% CI = 0.61-1.67, p = 0.97). We conclude that statins do not moderate the rate of development of mesothelioma in either a mouse model or a human cohort exposed to asbestos. © 2014 Robinson et al.